Cognitive Predictors of Precautionary Behavior During the COVID-19 Pandemic - Thoma, Volker; Weiss-Cohen, Leonardo; Filkuková, Petra; Ayton, Peter (Frontiers in Psychology, 2021)
The attempts to mitigate the unprecedented health, economic, and social disruptions caused by the COVID 19 pandemic are largely dependent on establishing compliance to behavioural guidelines and rules that reduce the risk of infection. Here, by conducting an online survey that tested participants’ knowledge about the disease and measured demographic, attitudinal and cognitive variables, we identify predictors of self-reported social distancing and hygiene behavior. To investigate the cognitive processes underlying health prevention behavior in the pandemic, we co-opted the dual process model of thinking to measure participants’ propensities for automatic and intuitive thinking versus controlled and reflective thinking. Self-reports of seventeen precautionary behaviours including regular hand-washing, social distancing and wearing a face-mask, served as a dependent measure. The results of hierarchical regressions showed that age, risk-taking propensity, and concern about the pandemic predicted adoption of precautionary behavior. Variance in cognitive processes also predicted precautionary behavior: participants with higher scores for controlled thinking (measured with the Cognitive Reflection Test) reported less adherence to specific guidelines, as did respondents with a poor understanding of the infection and transmission mechanism of the COVID-19 virus. The predictive power of this model was comparable to an approach (Theory of Planned Behaviour) based on attitudes to health behavior. Given these results we propose the inclusion of measures of cognitive reflection and mental model variables in predictive models of compliance and future studies of precautionary behaviour to establish how cognitive variables are linked with people’s information processing and social norms.